PROFIL KUALITAS HIDUP DAN TEKANAN DARAH PASIEN HIPERTENSI RAWAT JALAN DI RSUD ULIN BANJARMASIN - Riza Alfian; Nani Lisdawati; Aditya Maulana Perdana Putra; Ratih Pratiwi Sari; Fahma Lailani (Jurnal Ilmiah Manuntung, 2018)
Hypertension is one of the main factors of coronary heart disease and stroke. The prevalence of hypertension in South Kalimantan Province occupied a second prevalence of 30,8%. Hypertension is a chronic disease that requires long-term treatment. Furthermore, long-term treatment of anti-hypertension patients also have the possibility of side effects that also affect the quality of life of patients. Uncontrolled blood pressure can aggravate the incidence of hypertension and develop into a more dangerous disease that affects the quality of life of patients. The purpose of this study was to determine the description of blood pressure and quality of life of outpatient hypertensive patients at RSUD Ulin Banjarmasin. This research was conducted by using survey method. Sampling was done by consecutive sampling method. Samples meeting the inclusion criteria were 61 patients. The sample inclusion criteria were outpatients ages 18-65 with hypertension diagnoses, and were willing to follow the study. Exclusion criteria were patients with uncooperative, illiterate and deaf conditions. Data collection was done by interviewing and filling out the EQ-5D questionnaire. Blood pressure data were taken from medical records. The data of the research are presented in descriptive form. Based on this research can be concluded that the value of systolic blood pressure and diastolic mean of research sample is 153,82 ± 17,62 and 86,16 ± 10,52 mmHg. The study sample was dominated by patients with level II hypertension (52,5%). Furthermore the quality of life of the average sample was dominated by the category of poor quality of life (73,8%).